2017
DOI: 10.5527/wjn.v6.i5.236
|View full text |Cite
|
Sign up to set email alerts
|

Restless legs syndrome is contributing to fatigue and low quality of life levels in hemodialysis patients

Abstract: AIMTo examine whether hemodialysis (HD) patients with restless legs syndrome (RLS) are subjects of greater fatigue and impaired quality of life (QoL) compared to HD patients without RLS.METHODSEighty five stable HD patients participated in this study. According to their RLS status, the patients were divided into the RLS group (n = 23) and the non-RLS group (n = 62). QoL, fatigue, sleep quality, daily sleepiness and depression symptoms were assessed by using various questionnaires. Finally, biochemical paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
4
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 34 publications
0
15
4
2
Order By: Relevance
“…Published studies examining fatigue in CRF patients with RLS are scarce. In a study by Giannak et al, 28 involving 85 dialysis patients, RLS patients reported more severe fatigue, with positive correlations between the RLS severity scale and the fatigue index. When one considers that many HD patients experience intense fatigue symptoms, 29 it becomes clear that effective treatment of RLS, which contributes to fatigue symptoms, may help reduce the severity of fatigue.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Published studies examining fatigue in CRF patients with RLS are scarce. In a study by Giannak et al, 28 involving 85 dialysis patients, RLS patients reported more severe fatigue, with positive correlations between the RLS severity scale and the fatigue index. When one considers that many HD patients experience intense fatigue symptoms, 29 it becomes clear that effective treatment of RLS, which contributes to fatigue symptoms, may help reduce the severity of fatigue.…”
Section: Discussionmentioning
confidence: 92%
“…When one considers that many HD patients experience intense fatigue symptoms, 29 it becomes clear that effective treatment of RLS, which contributes to fatigue symptoms, may help reduce the severity of fatigue. 28 On the other hand, despite the presence of studies reporting the positive effects of exercise training on fatigue in HD patients, none specifically investigated patients with RLS. 29 Future studies may provide valuable insights on the effects of exercise in uremic patients with RLS.…”
Section: Discussionmentioning
confidence: 99%
“…These problems affect the different aspects of QOL [12]. In general, physical and social performance disorders decrease the QOL of HD patients [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Rohani et al reported that RLS is associated with insomnia, daytime sleepiness, shorter sleep duration, and using sedative-hypnotic medications [25]. Giannaki et al reported that fatigue is a prevalent symptom in chronic renal failure (CRF) patients, but it is more prominent in patients with RLS [26]. Fatigue can be related to impaired sleeping quality and decreased sleeping time in these patients [26].…”
Section: Complications Of Rls and Its Effect On Patient's Lifementioning
confidence: 99%
“…Giannaki et al reported that fatigue is a prevalent symptom in chronic renal failure (CRF) patients, but it is more prominent in patients with RLS [26]. Fatigue can be related to impaired sleeping quality and decreased sleeping time in these patients [26]. Another study by Giannaki et al found that hemodialysis patients with RLS showed atrophy in the thigh muscle compared to patients without RLS [18].…”
Section: Complications Of Rls and Its Effect On Patient's Lifementioning
confidence: 99%